Pre-operative physiotherapy for elderly patients undergoing abdominal surgery - Rozelle Labuschagne; Ronel Roos (AOSIS, 2022)
Background: Elderly patients report a decrease in function and activities of daily living following abdominal surgery. The objectives of our pilot study were to determine the effects of a single pre-operative physiotherapy session consisting of education and exercise on clinical and physical function outcomes in elderly patients. Methods/design: A single-blind pilot randomised controlled trial evaluated clinical and functional outcomes of elderly patients following surgery in a private hospital in Pretoria, South Africa. The outcomes included length of hospital stay (LOS), postoperative pulmonary complications (PPC), first mobilisation uptime, DeMorton Mobility Index (DEMMI), 6-minute walk test (6MWT), Lawton-Brody's instrumental activities of daily living (IADL) and the Functional Comorbidity Index (FCI). Descriptive and inferential statistics were undertaken, and statistical significance was set at p ≤ 0.05. Discussion: Twelve participants (n = 11 female [91.67%] and n = 1 [8.33%] male) with a mean age of 65.75 (±4.47) years were included. Most participants (n = 10, 83.33%) underwent lower abdominal laparotomy (n = 10, 83.33%). The median hospital LOS was n = 4 (IQR 3.25-4) days; walking distance at first mobilisation was 130 m (IQR (85-225), with intervention participants walking further (intervention: 177 m, IQR 100-242.50; control: 90, IQR 60 m - 245 m; p = 0.59). Recruitment was low, with only 10.95% referrals and 47.82% nonconsents. Conclusion: A single physiotherapy session prior to surgery demonstrated a potential favourable change in elderly patients' mobility postoperatively; however, further research is necessary. Clinical implication: A once-off pre-operative physiotherapy session could enhance recovery in elderly patients. Trial registration: Pan African Clinical Trial Registry, PACTR201809874713904, https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=3593